2008
DOI: 10.1080/15332640802083238
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Protective Factors for Binge Drinking Among Hispanic Subgroups in Florida

Abstract: This study examines differences in risk and protective factors for binge drinking among six ethnic/national subgroups of Hispanic adolescents in Florida. We note differences in the frequency of binge drinking by gender and ethnic subgroup as well as differences in the salience of items drawn from the five domains of risk and protective factors among these subgroups. Rather than treating all Hispanics as a unitary culture, tailoring of prevention programs to address risk and protective factors that differential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 11 publications
0
14
0
2
Order By: Relevance
“…Moreover, these traditional cultural values may serve both risk and protective functions for a variety of health behaviors. Research on the influence of cultural traditions and beliefs on health behavior has yielded significant associations with health-risk behaviors such as smoking, alcohol use, drug use, and sexual activity (Canino, Vega, Sribney, Warner, & Alegria, 2008; Chen & Unger, 1999; Cuadrado & Lieberman, 2002; Higgs et al, 2008; Prado et al, 2008; Siqueria & Crandall, 2008; Unger et al, 2002; Valdez, 2005; Valdez et al, 2008). Recently, Prado and colleagues found that the effects of “differential acculturation” among Hispanic families migrating into the United States contribute to a degenerative loss of traditional Hispanic cultural values, which in turn increases the risk of substance use behaviors for those with diminished cultural or familial ties.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, these traditional cultural values may serve both risk and protective functions for a variety of health behaviors. Research on the influence of cultural traditions and beliefs on health behavior has yielded significant associations with health-risk behaviors such as smoking, alcohol use, drug use, and sexual activity (Canino, Vega, Sribney, Warner, & Alegria, 2008; Chen & Unger, 1999; Cuadrado & Lieberman, 2002; Higgs et al, 2008; Prado et al, 2008; Siqueria & Crandall, 2008; Unger et al, 2002; Valdez, 2005; Valdez et al, 2008). Recently, Prado and colleagues found that the effects of “differential acculturation” among Hispanic families migrating into the United States contribute to a degenerative loss of traditional Hispanic cultural values, which in turn increases the risk of substance use behaviors for those with diminished cultural or familial ties.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Indeed, when these groups are divided into more specific categories based on national origin, there are typically large differences in substance use patterns across subgroups (An, Cochran, Mays, & McCarthy, 2008; Caraballo, Yee, Gfroerer, Pechacek, & Henson, 2006; Chen, Unger, Cruz, & Johnson, 1999; Lum, Corliss, Mays, Cochran, & Lui, 2009; Ma, Tan, Toubbeh, & Su, 2003; Siqueira & Crandall, 2008). More studies with sufficient statistical power are needed to take the additional step to subdivide the large categories (e.g., Asian or Hispanic subgroups based on national origin, or even more specific categorizations that take into account the interactions among culture of ancestry, culture of birth, and culture of residence).…”
Section: Limitations Of Previous Researchmentioning
confidence: 99%
“…This research may assist in the development of more effective and culturally sensitive model programs. Due to differences within subgroups in various parts of the country, it is recommended to amplify the availability of effective model programs for the Hispanic population through increasing research concerning differences within separate subgroups of the Hispanic population (Siqueira & Crandall, 2008). A recommendation for increasing the ability to recruit and retain samples of undocumented immigrants is to use the snowball effect in finding undocumented immigrants and to use anonymous surveys that do not include names or specific locations (such as community or Downloaded by [UQ Library] at 12:01 21 November 2014 town names) of participants.…”
Section: Recommendationsmentioning
confidence: 99%
“…Similar to these findings, Valdez, Mikow, and Cepeda (2006) reported that at risk Hispanic females were more likely to engage in alcohol and tobacco abuse when there is prevalence of family stress/conflict and weak family relationship. Siqueira and Crandall (2008) examined six subgroups of Hispanic adolescents in Florida, focusing on the differences in risk and protective factors for binge drinking. Researchers utilized data collected from the 2002 Florida Youth Substance Abuse Survey, which was implemented in middle schools and high schools in all 67 counties in Florida by four government agencies.…”
Section: Literature Reviewmentioning
confidence: 99%